Comparison of different application of mathematics online learning media in terms of critical thinking skills and learning interest - Oktapia, Penti; Hidayati, Kana (Jurnal Riset Pendidikan Matematika, 2022)
This study aims to determine: (1) whether students' critical thinking skills taking online learning through WhatsApp Group and learning videos on Facebook are higher on average than those who take online learning through WhatsApp Group and Google Meet. It is (2) whether the learning interest of students who take online learning through WhatsApp Group and learning videos on Facebook is higher on average than students who take online learning through WhatsApp Group and Google Meet. This research was a quasi-experimental research with a posttest-only non-equivalent control group design. All eighth-grade students are considered to be the population at the Masjid Syuhada Integrated Islamic Junior High School Yogyakarta in the 2020/2021 academic year. The research sample was students of class VIII A as the experimental class and class VIII C as the control class. The research instrument was in the form of a critical thinking skills test and student learning interest questionnaires. The hypothesis testing technique used is the Independent Sample T-Test. The study's results showed that the critical thinking skills of students who took online learning through WhatsApp Group and learning videos on Facebook was higher on average than those who took online learning through WhatsApp Group and Google Meet. Furthermore,  the learning interest of students who took online learning through WhatsApp Groups and learning videos on Facebook could be considered the same as students who took online learning through WhatsApp Groups and Google Meet.